Análisis de los factores motivacionales y su incidencia en el desempeño laboral en el personal del centro médico LojaSalud y la propuesta de un plan motivacional - Dalgo Córdova, Carlos Joel (2024)
This study focuses on how motivational factors influence the professional performance of LojaSalud Medical Center employees. It examines several theories of motivation, such as Maslow's hierarchy of needs, Herzberg's two-factor theory, Vroom's expectancy theory, and Deci and Ryan's self-determination theory. These theories provide a framework for understanding how needs, job satisfaction, expectations and self-actualization influence motivation and job performance. And in the context of LojaSalud employees, relevant motivational factors were identified, such as recognition, rewards, work-life balance, and opportunities for professional growth. The current situation of the LojaSalud medical center is specifically analyzed, evaluating working conditions and personal motivation through surveys and interviews. Based on these assessments, a specific motivational plan is proposed to improve employee motivation and well-being. This plan includes strategies based on motivation theories, such as implementing recognition and reward programs, strengthening communication and feedback, designing professional development plans and continuous training. It stresses the importance of evaluating and monitoring the plan to adjust it to needs and ensure its long-term effectiveness. In summary, this analysis identifies the main motivational factors in the work environment of the LojaSalud medical center and proposes a detailed plan to improve personal motivation, which is expected to result in improved performance and professional enrichment within the institution.